Labour Movements and State Formation in Turkey: Passive Revolution and Uneven Development (in English) - Sylvest, Jonas (International Gramsci Journal, 2023)
This article aims to apply the theory of Antonio Gramsci to labour-state relations in Turkey. More specifically it seeks to highlight the causes of political instability and the contradictory course of labour politics, mainly in the 1950-1980 period, from a Gramscian perspective. On the basis mainly of the Gramscian studies of Adam D. Morton (2011) and the Prison Notebooks of Antonio Gramsci (Gramsci 1971, 1975, 1992, 1996, 2007), the article illustrates how class struggles indicative to the formation of the modern Turkish state, within the conditions of uneven capitalist development, resulted in a political stalemate in the 1950s, 60s and 70s. Through the application of such concepts as passive revolution, uneven and combined development and the capitalist type of state, the author seeks to clarify how labour-state relations in Turkey are intrinsically linked to modern state formation. This involves the concomitant co-optation of labour movements and establishment of market relations, rooted in an international uneven and combined capitalist system.